Simultaneous Detection and Identification of Common Cell Culture Contaminant and Pathogenic Mollicutes Strains by Reverse Line Blot Hybridization - Wang, Hui (American Society for Microbiology, 2004)
We have developed a reverse line blot (RLB) hybridization assay to detect and identify the commonest mollicutes causing cell line contamination (Mycoplasma arginini, Mycoplasma fermentans, Mycoplasma hyorhinis, Mycoplasma orale, and Acholeplasma laidlawii) and human infection (Mycoplasma pneumoniae, Mycoplasma hominis, Mycoplasma genitalium, Ureaplasma parvum, and Ureaplasma urealyticum). We developed a nested PCR assay with “universal” primers targeting the mollicute 16S-23S rRNA intergenic spacer region. Amplified biotin-labeled PCR products were hybridized to membrane-bound species-specific oligonucleotide probes. The assay correctly identified reference strains of 10 mollicute species. Cell cultures submitted for detection of mollicute contamination, clinical specimens, and clinical isolates were initially tested by PCR assay targeting a presumed mollicute-specific sequence of the 16S rRNA gene. Any that were positive were assessed by the RLB assay, with species-specific PCR assay as the reference method. Initially, 100 clinical and 88 of 92 cell culture specimens gave concordant results, including 18 in which two or more mollicute species were detected by both methods. PCR and sequencing of the 16S-23S rRNA intergenic spacer region and subsequent retesting by species-specific PCR assay of the four cell culture specimens for which results were initially discrepant confirmed the original RLB results. Sequencing of amplicons from 12 cell culture specimens that were positive in the 16S rRNA PCR assay but negative by both the RLB and species-specific PCR assays failed to identify any mollicute species. The RLB hybridization assay is sensitive and specific and able to rapidly detect and identify mollicute species from clinical and cell line specimens.